ANALISIS PERENCANAAN JAMINAN MUTU SD MUHAMMADYAH 6 PALEMBANG - Elita, Desi; Mujahidin, Endin; Andriana, Nesia; Rahman, Imas Kania (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
Quality assurance in education is an important foundation in building a superior and sustainable learning system. This study examines the strategies and implementation of the quality assurance system at SD Muhammadiyah 6 Palembang, as well as its impact on the quality of the learning process and outcomes. Using a qualitative descriptive approach, data was collected through observation, interviews, and review of internal school documents. The findings indicate that school has developed a quality assurance system based on Islamic values and active involvement of school stakeholders. Internal supervision processes, teacher training, and school committee involvement are part of a planned quality improvement cycle. These findings emphasize that the success of quality assurance does not rely solely on administrative documents but also on a quality culture embedded throughout the school ecosystem. This study can serve as inspiration for educational institutions to ensure excellent and sustainable quality.